Haemoadsorption to remove inflammatory mediators in sepsis: past, present, and future - Nicole J. B. Waalders; Matthijs Kox; Peter Pickkers (Intensive Care Medicine Experimental)
Abstract While a dysregulated immune response is at the center of the sepsis definition, standard care is still solely focussed on prompt administration of antimicrobial therapy, source control, resuscitation and organ supportive therapies. Extracorporeal blood purification therapies, such as haemoadsorption, have been proposed as a possible adjunctive therapy to standard care in sepsis. These adsorption devices aim to rebalance the dysregulated immune response by removal of excessive amounts of circulating inflammatory mediators, including cytokines and endotoxins. Thus far, the effects of haemoadsorption on clinical outcomes have been insufficiently studied and although its routine use is not justified based on the current evidence, multiple centers use these devices in patients with severe septic shock. This narrative review describes the most well-studied adsorption devices as well as a novel selective adsorption device called the ‘IL-6-Sieve’, including in vitro data showing its capturing potential. Finally, it addresses important considerations for future trials on haemoadsorption in septic patients.